Establishment and characterization of stable, diverse, fecal-derived in vitro microbial communities that model the intestinal microbiota - Aranda-Díaz, Andrés; Ng, Katharine Michelle; Thomsen, Tani; Real-Ramírez, Imperio; Dahan, Dylan; Dittmar, Susannah; Gonzalez, Carlos Gutierrez; Chavez, Taylor; Vasquez, Kimberly S.; Nguyen, Taylor H.; Yu, Feiqiao Brian; Higginbottom, Steven K.; et al. (Cell host & microbe, 2022)
Efforts to probe the role of the gut microbiota in disease would benefit from a system in which patient-derived bacterial communities can be studied at scale. We addressed this by validating a strategy to propagate phylogenetically complex, diverse, stable, and highly reproducible stool-derived communities in vitro. We generated hundreds of in vitro communities cultured from diverse stool samples in various media; certain media generally preserved inoculum composition, and inocula from different subjects yielded source-specific community compositions. Upon colonization of germ-free mice, community composition was maintained, and the host proteome resembled the host from which the community was derived. Treatment with ciprofloxacin in vivo increased susceptibility to Salmonella invasion in vitro, and the in vitro response to ciprofloxacin was predictive of compositional changes observed in vivo, including the resilience and sensitivity of each Bacteroides species. These findings demonstrate that stool-derived in vitro communities can serve as a powerful system for microbiota research. [Display omitted] •Stool-derived in vitro communities (SICs) can be phylogenetically complex and reproducible•Mouse colonization with a SIC establishes near-native microbiota composition and host proteome•Antibiotic treatment in vivo increases susceptibility to Salmonella invasion in vitro•Antibiotic treatment in vitro mimics compositional changes in vivo Aranda-Díaz et al. demonstrate the utility of batch culturing of stool-derived in vitro communities (SICs) for low-cost, quantitative, and high-throughput experimentation on gut microbiotas. SICs retain the taxonomical diversity of their fecal origin and recapitulate the microbiota response to pathogen invasion and antibiotic treatment.